Prevalence of Burnout among Italian Nurses: a descriptive study: Italian Nursing Burnout - Vitale, Elsa; Cesano, Erika; Germini, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background and Aim: Job burnout is the psychosocial judgement of the physical and psychological tiredness result to the prolongation emotional pressure associated to the job. This study purposed to assess burnout prevalence among Italian nurses who worked in different contexts.Method: Burnout was assessed by the Italian version of the 22-item Maslach Burnout Inventory Human Service Survey. Data were collected in July and August 2019.Results: 300 Italian nurses voluntary participated in this study. Questionnaire were administered by Google Forms application, were all Italian nurses could participate.Conclusion: Emotional Exhaustion (EE) is the most representative dimension of burnout. This outcome becomes more acute with greater age and seniority in the position, due to the stress and monotony encountered and/or job dissatisfaction.